2020
DOI: 10.1101/2020.02.15.950287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AS-Quant: Detection and Visualization of Alternative Splicing Events with RNA-seq Data

Abstract: A simplistic understanding of the central dogma falls short in correlating the number of genes in the genome to the number of proteins in the proteome. Post-transcriptional alternative splicing contributes to the complexity of proteome and are critical in understanding gene expression. mRNA-sequencing (RNA-seq) has been widely used to study the transcriptome and provides opportunity to detect alternative splicing events among different biological conditions. Despite the popularity of studying transcriptome var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…1A and Suppl Table 1). We then profiled AS events using the custom-developed AS-Quant pipeline 22 . Strikingly, we found that chemical inhibition of mTOR in Table 2).…”
Section: Results and Discussion Mtor Activation Leads To Transcriptommentioning
confidence: 99%
See 1 more Smart Citation
“…1A and Suppl Table 1). We then profiled AS events using the custom-developed AS-Quant pipeline 22 . Strikingly, we found that chemical inhibition of mTOR in Table 2).…”
Section: Results and Discussion Mtor Activation Leads To Transcriptommentioning
confidence: 99%
“…Alternative splicing analysis was performed using the AS-Quant pipeline 22 . Briefly, the pipeline categorizes the alternative splicing events into cassette exon, mutually exclusive, alternative 5' splice site, and alternative 3' splice site.…”
Section: As-quant (Alternative Splicing Quantitation) Pipelinementioning
confidence: 99%